The Expansion of the Universe: Analysis and Evolution of a Great Discovery - Aguiar, Paulo (Fundamental Research and Application of Physical Science Vol. 2, 2023)
The expansion of the universe is one of the greatest discoveries of the 20th century. It is perhaps the most relevant fact discovered by man about his origins. On the other hand, until the identification of the cosmic microwave background radiation by Arnio Penzias and Robert Wilson in 1965, the recognition that the recession of distant galaxies increases with distance was the astronomical observation that most stimulated the birth of modern cosmology. This observational result is mainly associated with the American astronomer Edwin Hubble (1889-1953), who for this reason is often identified as the astronomer who discovered the expansion of the universe, as the discovery of the recession of distant galaxies was understood as proof of the expansion of the universe. In this context, it is his 1929 paper that is usually cited whenever the expansion of the universe is attributed to Hubble. However, on none of these pages does Hubble ever refer to the expansion of the universe. We will see, moreover, that the process that leads to this result is a long and complex one, in which several astronomers and theoretical physicists intervened, and whose interpretation is still the subject of heated debates. Here we will recall some of the authors and their respective works that most contributed to the idea of the expansion of the universe, as well as analyze some of their assumptions. We will then discuss the possibility that there are variants of the Standard Model compatible with current observations, taking into account the probable existence of heterogeneities in the distribution of matter in a very early period of the history of the universe.